Data Storage and Processing Information System in a Website-Based Quality Assurance Agency (BPM) (Case Study: National University): Data Storage and Processing Information System in a Website-Based Quality Assurance Agency (BPM) (Case Study: National University) - Syahril Ramadhan; Iwan Wahyuddin; Deny Hidayatullah (Jurnal Mantik, 2020)
At this time technology is a must in advancing performance in every organization and various other activities. One example of the application of technology that will be explained in this study is the design of information storage and data processing systems at the website-based quality assurance agency (BPM) at Nasional University. UPM by processing and storing it in the system to upload regulations made based on each access of UPM and online will be able to see the results of the Rector's Decree in public and can be downloaded as a PDF file. Previously in making reports from the Chancellor's Decree and other regulations, it still applied a manual system which could not be seen publicly and would take a lot of time and be less flexible. If UPM has made regulations for the Chancellor's Decree, it can be seen publicly where other UPMs can see the report of the Rector's Decree that has been made. In designing this web-based BPM system, the author uses the PHP programming language for the idea server and MYSQL for the database server. In addition, the Captcha system is used to verify first when logging into the BPM system. The purpose of the BPM system can be used as flexible processing and storage of regulations, making it easier to help speed up the process of activities more quickly.